Planning a preschool intervention in Finland - how to use digital technologies to increase community spirit and promote healthy energy balance-related behaviours? - Reetta Lehto; Reetta Lehto (Frontiers Media S.A., 2015)
Background: Energy balance-related behaviours (EBRBs) formed in childhood tend to persist into adulthood and thus it is important to promote healthy behaviours already at young age. In addition, socio-economic differences in EBRBs are already shown in small children. Thus it would be very important to tackle these differences in childhood and promote healthy EBRBs among children from low socio-economic status families. In order to succeed, strategies to motivate especially low socio-economic families need be used, e.g. by using social elements in interventions. Preschool could be an important setting to promote healthy behaviours among all children. In Finland over 70 % children attend preschool at ages 3-5 and the majority of children attend communal preschools. Aim(s): DAGIS intervention study aims to promote healthy EBRBs and to narrow socio-economic differences in these behaviours among preschool children. Digital technologies will be used in the intervention. Methods and results: Methods and specific aims of the intervention will be set after the results of the needs assessment (conducted in autumn 2015) and workshops for preschool personnel and parents (will be conducted in 2016) are analyzed. The intervention (2017-2018) will be conducted in preschools, and parents will be involved via preschools. Number of study children will be 800. We intend to use digital technologies/applications with a social element for families/preschools to help and motivate behavioral changes in EBRBs. A social element is needed because it is known to be an important motivator especially among low socio-economic groups, whereas individual elements are found to be ineffective (Cleland 2013, Bonevski 2014). Targeted EBRBs will be set later, but they could be e.g. sedentary behaviour, physical activity, fruit and vegetable intake and/or sugar intake. Conclusions: We plan a preschool intervention which aims to promote healthy EBRBs and diminish socio-economic differences in EBRBs among 3-6-year-old children. We intend to use digital technologies to help and motivate to change EBRBs. Suggestions and tips on possible digital technologies that can be used in the intervention are welcome!